Obtenção de sistemas microemulsionados e estudo de simulação por dinâmica molecular de sistemas micelares objetivando a veiculação de produtos naturais bioativos - Gomes, Fabiano do Espírito Santo (2010)
Among the new drugs launched into the market since 1980, up to 30% of them belong to the class of natural products or they have semisynthetic origin. Between 40-70% of the new chemical entities (or lead compounds) possess poor water solubility, which may impair their commercial use. An alternative for administration of poorly water-soluble drugs is their vehiculation into drug delivery systems like micelles, microemulsions, nanoparticles, liposomes, and cyclodextrin systems. In this work, microemulsion-based drug delivery systems were obtained using pharmaceutically acceptable components: a mixture Tween 80 and Span 20 in ratio 3:1 as surfactant, isopropyl mirystate or oleic acid as oil, bidistilled water, and ethanol, in some formulations, as cosurfactants. Self-Microemulsifying Drug Delivery Systems (SMEDDS) were also obtained using propylene glycol or sorbitol as cosurfactant. All formulations were characterized for rheological behavior, droplet size and electrical conductivity. The bioactive natural product trans-dehydrocrotonin, as well some extracts and fractions from Croton cajucara Benth (Euphorbiaceae), Anacardium occidentale L. (Anacardiaceae) e Phyllanthus amarus Schum. & Thonn. (Euphorbiaceae) specimens, were satisfactorily solubilized into microemulsions formulations. Meanwhile, two other natural products from Croton cajucara, trans-crotonin and acetyl aleuritolic acid, showed poor solubility in these formulations. The evaluation of the antioxidant capacity, by DPPH method, of plant extracts loaded into microemulsions evidenced the antioxidant activity of Phyllanthus amarus and Anacardium occidentale extracts. For Phyllanthus amarus extract, the use of microemulsions duplicated its antioxidant efficiency. A hydroalcoholic extract from Croton cajucara incorporated into a SMEDDS formulation showed bacteriostatic activity against colonies of Bacillus cereus and Escherichia coli bacteria. Additionally, Molecular Dynamics simulations were performed using micellar systems, for drug delivery systems, containing sugar-based surfactants, N-dodecylamino-1-deoxylactitol and N-dodecyl-D-lactosylamine. The computational simulations indicated that micellization process for N-dodecylamino-1- deoxylactitol is more favorable than N-dodecyl-D-lactosylamine system.